A Review of Maghemite Nanoparticles as Environmental Sensors - Imas Masriah; Devi Lestari; Prisca Caesa Moneteringtyas; Siti Mahmudha; Sulwiyatul Kamariyah Sani (INSOLOGI: Jurnal Sains dan Teknologi, 2025)
The increasing urgency to monitor and mitigate environmental pollution has driven significant interest in the development of advanced sensing technologies. Nanotechnology presents promising solutions through the application of nanoscale materials, among which maghemite nanoparticles (γ-Fe2O3) have garnered considerable attention due to their unique physicochemical properties, high chemical stability, a large specific surface area, and superparamagnetic behavior, making them suitable for separation, target deployment, and sensor regeneration. It functionalized maghemite nanoparticles to enhance their selectivity toward specific pollutants, including heavy metals ( e.g., Pb2+ and Cd2+) and toxic gases (e.g., NO, NH3, and H2S). These articles present a review of the structural and physicochemical characteristics of maghemite nanoparticles, including commonly applied synthesis methods, sensor mechanism, and their applications in pollutant detection, such as heavy metals and toxic gases. The review also highlights current challenges and outlines future directions for the development of more efficient, affordable, and sustainable maghemite-based sensors for next-generation environmental monitoring systems.